2020
DOI: 10.1515/ijamh-2019-0221
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk behaviors and influencing factors among Muslim adolescents on southern border of Thailand

Abstract: AbstractObjectivesTo describe individual, interpersonal, and environmental factors and sexual risk behaviors among Thai Muslim adolescents.MethodsWe recruited adolescents from four schools and one vocational college on the Southern border of Thailand during October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Based on the sex profile, most of the studies reported females to have higher levels of knowledge, awareness, attitude, and perception compared to males ( n = 7). It is to noted however that a fair comparison is not possible, as many of these studies had a skewed distribution whereby females outnumbered males [ 10 , 40 , 43 ]. Additionally, some of these studies also specifically targeted female participants [ 1 , 14 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the sex profile, most of the studies reported females to have higher levels of knowledge, awareness, attitude, and perception compared to males ( n = 7). It is to noted however that a fair comparison is not possible, as many of these studies had a skewed distribution whereby females outnumbered males [ 10 , 40 , 43 ]. Additionally, some of these studies also specifically targeted female participants [ 1 , 14 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some of these studies also specifically targeted female participants [ 1 , 14 , 39 ]. Nevertheless, some of the reasons provided by researchers for a lower level of knowledge and awareness among males include having a more uninvolved parenting style or lower parental monitoring, as well as more sex approval (for younger males/boys), and thus there is a lack of responsible communication on STIs among this cohort [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in USA found that more than half of US Muslim college students reported ever having had sexual intercourse, 30 while approximately 27.5% Muslim men in Ghana involved in high-risk sexual behavior. 18 In Thailand, a study in the southern border of Thailand (Muslim majority community) found that 9.0% schools and a vocational college students had experience of sexual intercourse 31 and 4.0% Muslim adolescent men in Ponok (private Islamic school) in Southern Thailand had premarital sexual intercourse. 20 The differences of the number observed among these studies may result from the local cultural influencing.…”
Section: Discussionmentioning
confidence: 99%